Rancang Bangun Prototipe Pengendali Pintu Air Berbasis SMS (Short Message Service) Untuk Pengairan Sawah Menggunakan Arduino - Handayani, Yanolanda Suzantry; Kurniawan, Adhadi (UNIB Press, 2020)
AbstrakCurrently opening and closing the floodgates for rice fields is still using the manual method, the manual method certainly still requires more effort to do this. Therefore it is necessary to develop a floodgate controller prototype using SMS (Short Message Service) with Arduino as the microcontroller, before making it into a larger form.This research uses experimental research methods. This research was conducted in the robotics laboratory of the Electrical Engineering Study Program, Faculty of Engineering, Bengkulu University. The results of the study, the time to send the fastest SMS when the fields need water is 10.21 seconds and the time to send the fastest SMS when the water needs for the fields is sufficient is 10.00 seconds using the Tri SIM card and the longest time to send SMS when the fields need water is 16.28 seconds and the sending time The longest SMS when the water requirement for rice fields is sufficient is 16.71 seconds using an Indosat SIM card. The performance of the floodgate controller prototype can open and close properly according to the command given via SMS service on the cellphone.Kata kunci: Module SIM800L, sensor ultrasonic, motor servo, Arduino Uno R3.